EVALUATION THROUGH E-GOVERNANCE IN EDUCATION - Kashif, Saadia; Saeed, Rabea (PEOPLE: International Journal of Social Sciences, 2019)
This study focuses on the importance of monitoring and evaluation in education through E-governance especially in low-budgeted educational institutions of Punjab, Pakistan. In this era of fast-paced world, monitoring and evaluation system for education needs to be revamped in terms of digitization for effective and efficient progression, results and follow-up (Sabbagh et al, 2012). There are some reference documents/frameworks available in Pakistan to evaluate and monitor schools, however, there is near to none collaboration among the public and private sector schools with respect to evaluation in education through e-governance. So, there is a need to answer that how ready is the education sector for e-governance in terms of monitoring and evaluation. Moreover, how effective it will prove to be a support for the school leadership to make informed decisions. To answer these questions, this research is expedited with the help of Hertzberg’s Two Factor (Motivation and Hygiene factors) Theory of Motivation (1968). The idea of digitized monitoring and evaluation was piloted in a cluster of 20 private (Primary and Secondary) schools with the help of Android Phones. This Data base has already been designed to generate reports as per the required formats, levels, and forms. This research provides direction to future evaluators and emphasize on the significance of digitization in educational monitoring and evaluation. It certainly has major implications for educators, evaluators and for the policy makers to implement e-governance through digitized monitoring and evaluation. Moreover, this unique idea of digitized monitoring enabled us to create paper free environment, have standardized and central monitoring, unified reporting formats, data base record keeping (safe and secure), and, access of data for evaluators and School Management Team (SMT).